Production of Edible Film from Isolate Soy Protein with Addition of Palmitic/Lauric Acids - Muhammad, Firnanda Rayyan; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2023)
On the structure, physical and functional properties of soy protein isolate/sodium alginate films, the influence of chain length and concentration of various fatty acids (palmitic acid and lauric acid) was evaluated. The fatty acid content of the films was validated by Fourier transform infrared spectroscopy. The opacity of films treated with fatty acids increases with increasing fatty acid chain length or concentration. The ability of a film to act as a moisture barrier is strongly influenced by the type and concentration of fatty acids. Films impregnated with stearic acid outperform other films in terms of effectiveness. Compared with films integrating stearic acid, those containing lauric acid showed greater elongation at break. Insoluble particles and greater roughness were seen in scanning electron micrographs of films containing fatty acids. These findings suggest that appropriate fatty acids can be used to create biopolymer-based films with the required characteristics. From this research it was found that the most optimal conditions for making edible film made from protein isolate with the addition of lauric acid and palmitic acid are a fatty acid ratio of 2:3, drying at a temperature of 75°C and drying for 3 hours to obtain a tensile strength value of 0.97 MPa and elongation of 24%.